Behavioural and emotional assessment of Malaysian adolescent boys with congenital colour vision deficiency and its association with socioeconomic factors - Belina-Anne William M. Thomas; Tharenee Ramakrishnan; Sharanjeet Sharanjeet-Kaur; Mahadir Ahmad; Lei Hum Wee; Mohd Izzuddin Hairol (PLoS ONE, 2026)
Congenital colour vision deficiency (CCVD) is associated with challenges in daily functioning and social interactions, yet its behavioural and emotional implications during adolescence remain underexplored. This study aimed to compare behavioural and emotional problems between adolescent boys with CCVD and those with normal colour vision (NCV) and to examine the influence of socioeconomic factors. A school-based cross-sectional comparative study was conducted where 44 boys with CCVD and 44 age- and class-matched NCV controls (aged 13–16 years) were identified through school-based vision screening. Colour vision status was confirmed using the Ishihara and Farnsworth D15 tests. Their parents completed the Child Behaviour Checklist (CBCL/4–18) to assess Internalising Problems, Externalising Problems , and Total Problems , as well as narrow-band syndromes. Data were analysed using Mann–Whitney U tests and chi-square analyses. Adolescents with CCVD scored significantly higher on most CBCL/4–18 narrow-band scales ( Anxious/Depressed, Withdrawn, Thought Problems, Attention Problems, Delinquent Behaviour, Aggressive Behaviour ), broad-band scales (Internalising Problems and Externalising Problems ), and Total Problems (all q < 0.05). Attention Problems showed the strongest association with CCVD status. Categorical analysis revealed that CCVD status was significantly associated with classification in the Borderline Clinical/Clinical range for Externalising Problems, Attention Problems, Anxious/Depressed, Aggressive Behaviour , and Total Problems . Among boys with CCVD, those whose parents had tertiary education demonstrated higher proportions of behavioural difficulties in the Externalising Problems and Total Problems domains; however, these findings should be interpreted with caution due to the small subgroup size. Lower household income was significantly associated with Withdrawn, Anxious/Depressed, Thought Problems, and Aggressive Behaviour scores (all q < 0.05). In conclusion, the results indicate that psychosocial and environmental factors may influence behavioural outcomes in children with CCVD, highlighting the importance of early identification and supportive interventions.